Poly-β-Hydroxybutyrate Turnover in Azorhizobium caulinodans Is Required for Growth and Affects nifA Expression - Mandon, Karine (American Society for Microbiology, 1998)
Azorhizobium caulinodans is able to fix nitrogen in the free-living state and in symbiosis with the tropical legume Sesbania rostrata. The bacteria accumulate poly-β-hydroxybutyrate (PHB) under both conditions. The structural gene for PHB synthase, phbC, was inactivated by insertion of an interposon. The mutant strains obtained were devoid of PHB, impaired in their growth properties, totally devoid of nitrogenase activity ex planta (Nif(−)), and affected in nucleotide pools and induced Fix(−) nodules devoid of bacteria. The Nif(−) phenotype was the consequence of the lack of nifA transcription. Nitrogenase activity was partially restored to a phbC mutant by constitutive expression of the nifA gene. However, this constitutive nifA expression had no effect on the nucleotide content or on growth of the phbC mutant. It is suggested that PHB is required for maintaining the reducing power of the cell and therefore the bacterial growth. These observations also suggest a new control of nifA expression to adapt nitrogen fixation to the availability of carbon and reducing equivalents.